REALISASI PROGRAM CSR (Corporate Social Responsibility) PT. LAJU PERDANA INDAH TERHADAP MASYARAKAT DESA MELUAI KECAMATAN CEMPAKA DI KABUPATEN OKU TIMUR - Sugeng Suprianto, Tiyas Murtiningsih, Neng Karmila, Anggi Fatmayati (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2025)
Corporate Social Responsibility (CSR) is a way for a company to achieve balance in terms of economy, environment, and social issues, so that it can fulfill stakeholder desires. This study aims to analyze the realization of CSR of PT. Laju Perdana Indah as a sugarcane plantation company in Meluai Village, Cempaka District, East Ogan Komering Ulu (OKU) Regency. The research method used in this study is the case study method. Sampling from the entire population using the simple random sampling method, namely the Meluai Village community as many as 30 people. The objectives of the study were analyzed using a quantitative descriptive method using the Likert Scale. The results of the study indicate that the realization of the CSR program of PT. Laju Perdana Indah is quite effective.